In Vivo Secretion of β-Lactamase-Carrying Outer Membrane Vesicles as a Mechanism of β-Lactam Therapy Failure - Bielaszewska, Martina; Daniel, Ondřej; Nyč, Otakar; Mellmann, Alexander (Membranes, 2021)
Outer membrane vesicles carrying β-lactamase (βLOMVs) protect bacteria against β-lactam antibiotics under experimental conditions, but their protective role during a patient's treatment leading to the therapy failure is unknown. We investigated the role of βLOMVs in amoxicillin therapy failure in a patient with group A Streptococcus pyogenes (GAS) pharyngotonsillitis. The patient's throat culture was examined by standard microbiological procedures. Bacterial vesicles were analyzed for β-lactamase by immunoblot and the nitrocefin assay, and in vivo secretion of βLOMVs was detected by electron microscopy. These analyses demonstrated that the patient's throat culture grew, besides amoxicillin-susceptible GAS, an amoxicillin-resistant nontypeable Haemophilus influenzae (NTHi), which secreted βLOMVs. Secretion and β-lactamase activity of NTHi βLOMVs were induced by amoxicillin concentrations reached in the tonsils during therapy. The presence of NTHi βLOMVs significantly increased the minimal inhibitory concentration of amoxicillin for GAS and thereby protected GAS against bactericidal concentrations of amoxicillin. NTHi βLOMVs were identified in the patient's pharyngotonsillar swabs and saliva, demonstrating their secretion in vivo at the site of infection. We conclude that the pathogen protection via βLOMVs secreted by the flora colonizing the infection site represents a yet underestimated mechanism of β-lactam therapy failure that warrants attention in clinical studies.
Keywords: in vivo secretion; Haemophilus influenzae; amoxicillin therapy failure; GAS protection; pharyngotonsillitis; β-lactamase-carrying outer membrane vesicles; group A Streptococcus pyogenes (GAS)